Effect of phosphorus deficiency on growth and trasport of k+, na+, cl-, no3- in lentil seedling (lens culinaris medik. Var. Barimasur-4) (Dhaka University Journal of Biological Sciences, 2011)
Effects of phosphorus deficiency on accumulation of dry matter and transport of some monovalent ions viz., Na+, K+, Cl- , and NO3- in lentil showed that seedlings raised in culture solution with and without different amount of phosphorus decreased accumulation of K+ and increased accumulation of Na+ in both the root and shoot of lentil. Cl– contents increased under P?deficiency. Concentration of NO3- was increased in the root and decreased in the shoot of P?deficient lentil. P-deficiency caused an increase in the root dry matter and a decrease in the shoot. P-deficiency resulted in a decrease in the shoot : root. Key words: P-deficiency; Growth; Transport; Na+; K+; Cl–; NO3–; Lentil, DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8967 DUJBS 2011; 20(2): 103-108